Monitoring Volcanic Eruptions with Geographical Information Systems and Remote Sensing Methods: The Case Study of Cumbre Vieja Volcano (Spain) - Özer Akyürek (Doğal Afetler ve Çevre Dergisi)
Natural disasters are defined as events that cause various losses for people and affect all living things by interrupting life. Volcanoes have affected natural life in various ways, from the existence of the earth to the present. While they have benefits in various aspects (heating-geothermal waters, etc.), they also have harmful effects. Volcanic eruptions, one of the natural disasters, have caused many destructions and deaths throughout human history and continue to do so. In today's technology, Geographical Information Systems and Remote Sensing tools are used as an integral part of management and monitoring for monitoring volcanic disasters. GIS and Remote Sensing are used as modern and useful data collection and processing, analysis, querying, and updating tools. In this study, it was aimed to examine the effects of lava from Cumbre Vieja volcano on La Palma island on people, structures and land cover, using Pleiades-1A, CosmoSky Med, GeoEye-1 and Landsat 8 data between 19 September and 15 November 2021. It was determined that the lava coming out of the volcano spread over an area of 1,042.07 hectares. In this area, it was revealed in the analyzes that 2,749 buildings were destroyed or partially damaged. The length of the damaged transportation lines reached 80.1 km. The Land surface temperature analysis, the temperature changes of the region before and after the explosion were examined. As a result of the GIS and UA analyzes, it was determined that various agricultural areas and forest areas, as well as residential areas and the ocean, were also damaged.